The role of RIM in neurotransmitter release: promotion of synaptic vesicle docking, priming, and fusion - Wu, Shanshan; Fan, Jiali; Tang, Fajuan; Chen, Lin; Zhang, Xiaoyan; Xiao, Dongqiong; Li, Xihong (Frontiers in Neuroscience, 2023)
There are many special sites at the end of a synapse called active zones (AZs). Synaptic vesicles (SVs) fuse with presynaptic membranes at these sites, and this fusion is an important step in neurotransmitter release. The cytomatrix in the active zone (CAZ) is made up of proteins such as the regulating synaptic membrane exocytosis protein (RIM), RIM-binding proteins (RIM-BPs), ELKS/CAST, Bassoon/Piccolo, Liprin-α, and Munc13-1. RIM is a scaffold protein that interacts with CAZ proteins and presynaptic functional components to affect the docking, priming, and fusion of SVs. RIM is believed to play an important role in regulating the release of neurotransmitters (NTs). In addition, abnormal expression of RIM has been detected in many diseases, such as retinal diseases, Asperger’s syndrome (AS), and degenerative scoliosis. Therefore, we believe that studying the molecular structure of RIM and its role in neurotransmitter release will help to clarify the molecular mechanism of neurotransmitter release and identify targets for the diagnosis and treatment of the aforementioned diseases.